2019
DOI: 10.3390/f10050382
|View full text |Cite
|
Sign up to set email alerts
|

Examining Changes in Stem Taper and Volume Growth with Two-Date 3D Point Clouds

Abstract: Exact knowledge over tree growth is valuable information for decision makers when considering the purposes of sustainable forest management and planning or optimizing the use of timber, for example. Terrestrial laser scanning (TLS) can be used for measuring tree and forest attributes in very high detail. The study aims at characterizing changes in individual tree attributes (e.g., stem volume growth and taper) during a nine year-long study period in boreal forest conditions. TLS-based three-dimensional (3D) po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 52 publications
0
27
1
Order By: Relevance
“…Furthermore, data acquisition from conservation areas, for example, is only possible when destructive measurements are not required. Finally, multi-temporal TLS measurements enable monitoring of stem taper over time [56].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, data acquisition from conservation areas, for example, is only possible when destructive measurements are not required. Finally, multi-temporal TLS measurements enable monitoring of stem taper over time [56].…”
Section: Discussionmentioning
confidence: 99%
“…Terrestrial laser scanning (TLS) has proven to non-destructively provide three-dimensional (3D) information on tree stems (Liang et al 2014, Kankare et al 2013, Raumonen et al 2013, Saarinen et al 2017) that has been impractical to produce with traditional means such as calipers or measurement tape. In applications related to boreal forests, TLS has been utilized in quantifying stem growth and changes in stem taper (Luoma et al 2019), reparametrizing an existing taper curve model , and assessing timber quality ).…”
Section: Background and Summarymentioning
confidence: 99%
“…Although it has been demonstrated that TLS technology can be used for detecting structural changes in single trees as well as changes in the canopy structure [30][31][32][33][34][35], there is still a limited understanding on how different kinds of forest structural changes can be quantified using TLS in boreal forest conditions. Srinivasan et al [30] used TLS data from two time points (2009 and 2012) for modeling tree biomass changes in East Texas.…”
Section: Introductionmentioning
confidence: 99%